Marketing estratégico para la comercialización de impresoras 3D genéricas en la ciudad de Guayaquil - Cordero Murillo, Jimmy Alexander (2023)
In today's era, 3D printing technology has emerged as a transformative force in fields ranging from manufacturing to medicine to education. However, in the city of Guayaquil, Ecuador, a major economic and cultural center, 3D printer adoption remains limited due to a lack of awareness and low accessibility of affordable products in the local market. To address this technological and educational gap, a strategic digital marketing campaign is proposed to promote 3D printers in Guayaquil. The research is based on a detailed analysis of the current market situation, the background of 3D printing technology, and the specific challenges facing the city. The objective is to offer effective and measurable solutions to boost the adoption and understanding of 3D printers in the Guayaquil community. The research seeks to contribute to the technological and economic advancement of the city, as well as to empower individuals and companies to explore and take advantage of the possibilities of 3D printing in their search for innovation and development. By overcoming obstacles, the campaign could open up new opportunities for local industry and promote the use of 3D printers in key sectors such as manufacturing, education and medicine. In addition, the initiative is expected to foster the creation of communities of knowledge and collaboration around 3D printing technology in Guayaquil. The successful implementation of this campaign could accelerate the adoption of 3D printers in Guayaquil and, in turn, improve the city's competitiveness in the global arena. It would also allow individuals and companies to take full advantage of the benefits of this cutting-edge technology to drive innovation and development in the region.